Sports coaching a theoretical and practical guide - Cope, Ed; Partington, Mark (Routledge, 2020)
The application of the theoretical underpinnings of coaching to practice are a central concern in sport. How should academic research seek to inform applied practice, and how should practicing coaches integrate research into their professional activities? Sports Coaching: A Theoretical and Practical Guide is the first book to truly integrate academic research on sports coaching with an assessment of and recommendations for applied practice. With every chapter written by a coaching researcher and a practicing, elite-level coach, the book clearly and concisely introduces the academic evidence base and discusses how and why theory should be integrated into practice. Made up of sections on coaching practice, coach education and development, the use of sport science support, and coaching special populations, the book constitutes a complete guide to the theory and practice of sports coaching. Chapters are clearly and consistently structured, allowing students and coaches to gain a firm understanding of the core theoretical principles of sports coaching and the ways in which they can and should guide practice. The book is a vital resource for any sports coaching student, researcher or practitioner to develop their evidence-based practice